Transapical Transcatheter Aortic Valve Implantation Using the JenaValve: A One-Year Follow-up - Reuthebuch, Oliver; Koechlin, Luca; Kaufmann, Beat A.; Kessel-Schaefer, Arnheid; Gahl, Brigitta; Eckstein, Friedrich S. (The Thoracic and Cardiovascular Surgeon, 2015)
Objective Since the first transcatheter aortic valve implantation (TAVI) in 2002, TAVI technique has gained an increasing popularity especially in high-risk patients. In this study, we present the first echocardiographic midterm outcome with the second-generation transapical JenaValve TAVI system (JenaValve Technology GmbH, Munich, Germany) in patients with aortic stenosis (AS).Methods Between November 2011 and November 2012, a total of 28 patients received transapical TAVI using the JenaValve. Primary endpoint was a combined efficacy endpoint after 1 year, which included all-cause mortality after more than 30 days, failure of current therapy for AS requiring hospitalization for symptoms of valve-related cardiac decompensation or prosthetic heart valve dysfunction. Moreover, we analyzed secondary endpoints after 3 and 12 months including cardiovascular mortality; major stroke; and life-threatening, disabling, or major bleeding. Mean echocardiographic follow-up was 471.35 ± 102.72 days.Results Mean age was 80.43 ± 6.03 years and EuroSCORE II was 8.80 ± 7.21%. Successful implantation was accomplished in 100% (n = 28). Median transvalvular aortic mean pressure gradient was 44.5 mm Hg (interquartile range [IQR]: 34.5; 55.5) preoperatively, 12 mm Hg (IQR: 9; 16) postoperatively, and 11 mm Hg (IQR: 8; 16) after 1 year. After 12 months, no paravalvular leakage was seen in 52.38% of the patients and grade 1 paravalvular leakage was seen in 47.62% of the patients. There was no grade 2 or 3 leakage detected. Stroke, valve thrombosis or dislocation, myocardial infarction, or bleeding was also not observed. However, criteria for the combined efficacy endpoint after 1 year were met in five patients (17.86%). Thirty-day mortality was 14.29% (n = 4) and all-cause mortality after 1 year was 21.43% (n = 6).Conclusion The JenaValve transapical TAVI system is a safe and feasible procedure with low peri- and postoperative complications and convincing midterm performance of the prosthesis.
Keywords: aortic valve and root; heart valve; transapical; TAVI; outcomes